2016
DOI: 10.1371/journal.pone.0157971
|View full text |Cite
|
Sign up to set email alerts
|

Alarm Variables for Dengue Outbreaks: A Multi-Centre Study in Asia and Latin America

Abstract: BackgroundWorldwide, dengue is an unrelenting economic and health burden. Dengue outbreaks have become increasingly common, which place great strain on health infrastructure and services. Early warning models could allow health systems and vector control programmes to respond more cost-effectively and efficiently.Methodology/Principal FindingsThe Shewhart method and Endemic Channel were used to identify alarm variables that may predict dengue outbreaks. Five country datasets were compiled by epidemiological we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 71 publications
2
87
0
13
Order By: Relevance
“…The findings of the study support the existing evidence on the association between weather variables and dengue incidence [57,58,59,60]. Many studies have identified an overall increased risk of dengue for rainfall and temperature at lag weeks 9–16 [21,61].…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the study support the existing evidence on the association between weather variables and dengue incidence [57,58,59,60]. Many studies have identified an overall increased risk of dengue for rainfall and temperature at lag weeks 9–16 [21,61].…”
Section: Discussionsupporting
confidence: 84%
“…In particular in Argentina there are interesting experiences on this issue, for example [28,29,30] deal with Dengue epidemics from the dynamic point of view, while [31] are concerned with the deployment of operational tools for its management. At a global scope we can find interesting contributions [32,33,34] with also some operatives experiences [35] Specifically, in a interinstitutional framework between the Argentinean National Space Agency (CONAE) and the Health Ministry of Argentina, there have been initiatives to model the temporal evolution of mosquito populations using environmental variables obtained from remote sensors. These works used series of a few years and are based on a small number of satellite variables [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, es importante que los sistemas de vigilancia epidemiológica y de salud ambiental incorporen estrategias que alcancen a la población que circula entre ciudades con dengue endémico para poder reducir las posibilidades de propagación. Varias prácticas básicas, tales como la piscicultura para reducir el vector y su larva, el uso de repelentes o la notificación veloz a los servicios de salud de síntomas asociados al dengue pueden ayudar a reducir las epidemias, en conjunto con las acciones tradicionales implementadas por agentes sanitarios: el control de basura amontonada, piscinas no cuidadas, tanques de agua sin tapa, floreros y abrevaderos, entre otros sitios favorables para la proliferación de mosquitos (30) .…”
Section: Discussionunclassified